Factors related to Low Back Pain (LBP) in Jambi City Health Service employees in 2025 - Ghina Salsabila; Guspianto Guspianto; Rizalia Wardiah; Willia Novita Eka Rini; Budi Aswin (CV. AFDIFAL MAJU BERKAH, 2025)
Low Back Pain (LBP) is a common phenomenon and a frequent complaint among office workers. According to data from the World Health Organization (WHO), 1.7 billion people worldwide suffer from musculoskeletal disorders, with 17.3 million of them experiencing Low Back Pain (LBP). Therefore, the aim of this study is to identify the factors associated with Low Back Pain (LBP) among employees of the Jambi City Health Office. This research used a cross-sectional design with a chi-square test. A total of 99 respondents were selected using purposive sampling. The variables examined included age, length of employment, physical activity (exercise), and work posture. The results showed significant associations between age (p = 0.003), physical activity (exercise) (p = 0.001), and work posture (p = 0.022) with complaints of Low Back Pain (LBP), while no significant association was found between length of employment (p = 0.546) and complaints of Low Back Pain (LBP). Age was found to have the greatest influence on complaints of Low Back Pain (LBP) (PR = 1.519), indicating that employees aged ≥ 35 years are 1.519 times more likely to experience Low Back Pain (LBP) compared to those under 35 years old